Profitabilitas, Pertumbuhan pada Struktur Modal, dan Ukuran Perusahaan sebagai Variabel Pemoderasi - Hotama, Anak Agung Istri Jayanti; Gede Wirama, Dewa (E-Jurnal Akuntansi; Vol 33 No 9 (2023)DO - 10.24843/EJA.2023.v33.i09.p07, 2023)
The purpose of this study is to provide empirical evidence regarding the effect of profitability and growth on the capital structure with firm size as moderating variable. This research was conducted on non-financial companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2020 period. 59 companies with three years of observation period were selected, resulting in a sampel of 177 firm-year. Using non-probability sampling with purposive sampling technique, this study used moderated regression analysis technique. The results of the analysis show that profitability and growth had a positive effect on capital structure, and that firm size moderates the effect of profitability and growth on the capital structure of non-financial companies listed on the Indonesia Stock Exchange for the 2018-2020 period. Keywords: Profitability, Growth, Size, Capital Structure.